Additive effectiveness and feasibility of a theory-driven instant assessment and feedback system in brief cannabis intervention: A randomised controlled trial. (February 2021) - Papinczak, Zoë E.; Connor, Jason P.; Feeney, Gerald F.X.; Gullo, Matthew J.
Abstract: Assessment and personalised feedback are important components of brief interventions (BIs) for cannabis use. A key outcome is to increase motivation to change during this short interaction. The diversity of available assessments and time burden scoring them pose a challenge for routine use in clinical practice. An instant assessment and feedback (iAx) system was developed to administer assessments informed by bioSocial Cognitive Theory, that were instantly scored and benchmarked against clinical norms, to provide patient feedback and guide treatment planning. This study evaluated the feasibility and additive effectiveness of the iAx on motivation to change cannabis use, when compared to treatment as usual (TAU), in a single-session BI. A randomised controlled trial was conducted in a public hospital alcohol and drug outpatient clinic. Eighty-seven cannabis users ( M age = 26.41; 66% male) were assigned to the BI utilising the iAx (iAx; n = 44) or to the standard BI (TAU; n = 43). Patients completed pre- and post-BI assessments of motivation to change and a post-BI measure of treatment satisfaction. Practitioners completed a feedback survey. Patients receiving iAx reported a significantly greater increase in motivation to change from pre- to post-BI compared to patients receiving TAU ( d = 0.49, p = .03). Treatment satisfaction was high across both conditions, with no significant difference between groups ( p = .57). Practitioners also reported a high level of satisfaction with the iAx system. In summary, findings support the feasibility and additive effectiveness of the iAx to enhance patient motivation during cannabis BI.